Evaluation of the accuracy of conventional and digital implant impression techniques in bilateral distal extension cases: a randomized clinical trial - Wafaa Youssef Elashry; Mohamed Maamoun Elsheikh; Ali Mohamed Elsheikh (BMC, 2024)
Abstract Background This clinical study aims to evaluate the accuracy of the conventional implant impression techniques compared to the digital impression ones in bilateral distal extension cases. Methods A total of 32 implants were placed in eight patients missing all mandibular posterior teeth except the first premolars. Each patient received a total of four implants, with two implants placed on each side, in order to provide support for three units of screw-retained zirconia restorations. Following osteointegration, the same patient underwent two implant-level impression techniques: Conventional open-tray impressions CII (splinted pick-up) and digital implant impressions DII with TRIOS 3 Shape intraoral scanner. The accuracy of impressions was evaluated utilizing a three-dimensional superimposition analysis of standard tessellation language (STL) files. Subsequently, the scan bodies were segmented using Gom inspect software to measure three-dimensional deviations in a color-coding map. Data were statistically analyzed using the Kruskal Wallis test and then a post-hoc test to determine the significance level (P < 0.05). Results The study revealed that higher angular and positional deviations were shown toward distal scan bodies compared to mesial ones for both impression techniques. However, this difference was not statistically significant (P > 0.05). Conclusion Splinted open-tray conventional impression and intraoral scanning implant impression techniques have demonstrated comparable accuracy. Trial registration Clinical Trials.gov Registration ID NCT05912725. Registered 22/06/ 2023- Retrospectively registered, https://register.clinicaltrials.gov .